2013
DOI: 10.1002/clen.201300247
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene Biodegradation by Pseudomonas xanthomarina Isolated from an Aged Contaminated Soil

Abstract: 17The bacterial community of a soil contaminated by a mothball chemical industry mainly 18 consisted of Betaproteobacteria and Gammaproteobacteria (with Achromobacter spp. 19and Pseudomonas spp., respectively, as the most representative genera). Upon 20 addition of phenanthrene, species of these two genera were found in the enrichment 21 cultures as well as among the isolated strains. The isolated bacteria were tested for 22 phenanthrene degradation, but only Pseudomonas xanthomarina, either as single 23 cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…For bacteria, the Proteobacteria , particularly the Gammaproteobacteria , increased considerably with increasing contamination. These findings are consistent with many previous studies that have demonstrated the hydrocarbon degradation potential of many members of this class (Arun et al, 2008 ; Sopeña et al, 2013 ). Notably, the family Sinobacteraceae (Gutierrez et al, 2013 ) and the order PYR10d3 (Singleton et al, 2006 ), which have been associated with hydrocarbon degradation in previous studies, increased with contamination.…”
Section: Discussionsupporting
confidence: 93%
“…For bacteria, the Proteobacteria , particularly the Gammaproteobacteria , increased considerably with increasing contamination. These findings are consistent with many previous studies that have demonstrated the hydrocarbon degradation potential of many members of this class (Arun et al, 2008 ; Sopeña et al, 2013 ). Notably, the family Sinobacteraceae (Gutierrez et al, 2013 ) and the order PYR10d3 (Singleton et al, 2006 ), which have been associated with hydrocarbon degradation in previous studies, increased with contamination.…”
Section: Discussionsupporting
confidence: 93%
“…S4 d) over a period of 21 days. The ability of various bacteria to degrade naphthalene, including Sphingomonas, Pseudomonas and Acidovorax, has been reported 24 , 26 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas spp. (Betaproteobacteria) was not selected since it is a very known PAH degrader (Sopeña et al, 2013). Only two of the six strains selected showed a significant biodegradation capacity for FLU and PYR (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%